Effect of a commercial blend of essential oils on productive parameters of broilers - Córdova-Terán, Hugo Eduardo (2024)
The aim of this study was to determine the effect of a commercial mixture of essential oils (Mix–Oil®) on the productive parameters of Cobb 500 broilers. The work was carried out in a 40 m2 shed located in the Chongón parish, Guayas, Ecuador. In total, 400 male broiler chickens were placed in 40 polyethylene cages with a population density of 10 chickens.m-2. The supplementation of the commercial essential oil mixture Mix–Oil® in the water was compared against a treatment without application, distributed in two groups at random. Feed consumption, weight gain, feed conversion, water consumption, morbidity and mortality were evaluated. Supplementation with essential oils did not affect feed consumption; however, there was a tendency to generate lower body weight and lower weight gain in the initial stages of the productive cycle. The Mix–Oil® essential oil blend reduced morbidity during the growing stage and improved feed conversion (1.70), weekly weight gain (852 g.bird-1) and reduced water consumption during the finishing period of Cobb 500 chickens.